Anticancer activity of ethyl acetate and n-butanol extracts from rhizomes of Agapetes megacarpa W.W. Smith - Jariya Alongkornsopit (2018)
Agapetes megacarpa W.W. Smith, also known as Pratat Doi, is one of the commonly used medicinal herbs in northern Thailand. The water extract of the herb has been used for lactation and body shapeup by gestation women. Toxicity and antitumor activities of this herb have never been reported. The objective of this study was to examine the cytotoxic and antitumor activities of ethyl acetate and nbutanol partitioned extracts prepared from the rhizomes of this herb. The breast cancer cell lines, MCF- 7 and MDA-MB231 and the lung cancer cell line NCI-H1299 were used. The cells were exposed to serial concentrations of the extracts in dimethylsulfoxide and dissolved in cell culture medium. Cytotoxic and antiproliferative assays were used employing the Sulforhodamine B method. The experiments showed that, none of the extracts expressed acute cytotoxicity to the cancer cells within 24 h. Antiproliferative effect was exhibited with time-and concentration-dependent manner after 5 days of exposure. Apoptotic induction on the cancer cell lines was analyzed by flow cytometry using Annexin-V-FITC/propidium iodide staining. Significant differences of apoptotic percentages were found from the exposed cells to both of the extract partitions when compared with the unexposed control cells. The results implied bioactive apoptotic induction by constituents contained in the more polar solvent partition. © 2011 Academic Journals.